2017
DOI: 10.1590/1678-4162-8722
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of acute phase proteins in goats and ewes with naturally acquired Staphylococcus aureus mastitis

Abstract: Serum protein concentrations, including acute phase proteins (APPs), of goats and ewes with naturally acquired Sthaphylococcus aureus mastitis were determined by means of SDS-PAGE electrophoresis to evaluate the relevance of these APPs as biomarkers of the disease in these species. Fifteen healthy goats and 5 goats with naturally acquired staphylococci mastitis, as well as fifteen healthy ewes and 5 ewes with staphylococci mastitis were submitted to daily blood sampling during 7 days. In goats, an increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This study demonstrated a marked increase in APPs (Fb, Cp, SAA, and Hp) concentrations in CMG. Similar observations were reported before for mastitis in camels and other animal species [ 15 , 19 21 ]. Additionally, the pro-inflammatory cytokines prompt free radicals liberation from different immune cells.…”
Section: Discussionsupporting
confidence: 90%
“…This study demonstrated a marked increase in APPs (Fb, Cp, SAA, and Hp) concentrations in CMG. Similar observations were reported before for mastitis in camels and other animal species [ 15 , 19 21 ]. Additionally, the pro-inflammatory cytokines prompt free radicals liberation from different immune cells.…”
Section: Discussionsupporting
confidence: 90%
“…Normal haptoglobin concentrations for adult goats range between 0.39 and 1.26 g/L (Heller and Johns, 2015;Saidu et al, 2016), which can increase to 1.70 g/L with mastitis (Simplício et al, 2017), which causes inflammation of the mammary tissues and is considered to be painful (Leslie and Petersson-Wolfe, 2012;Fitzpatrick et al, 2013). The values we observed following clove oil injections were substantial, highlighting potentially undesirable side effects.…”
Section: Discussionmentioning
confidence: 79%
“…Regarding ovine mastitis, to our knowledge, there are only two studies investigating APP response in case of naturally occurring mastitis [28,72], but the studies are not complex, since they investigated the APP concentration only in one diagnostic matrix, Simplicio et al [72] in serum, while Miglio et al [28] in milk. There is also a complex study investigating the protein profile changes in ewes experimentally infected with Mannheimia haemolytica [73], which reveals that after bacterial inoculation the protein profile of blood plasma as well as milk changed significantly.…”
Section: Acute-phase Proteinsmentioning
confidence: 99%
“…For example, in ewes blood plasma there were identified 33 differentially abundant proteins (compared to findings before the challenge): 6 with decrease, 13 with new appearance, and 14 with varying abundance [73] including acute-phase proteins. Simplicio et al [72] investigated serum APP concentration in ewes and goats with naturally acquired staphylococcal mastitis and claimed that increase in serum ceruloplasmin, fibrinogen, haptoglobin, and α1-acid glycoprotein was of 337%, 90%, 461%, and 225%, respectively. While Miglio et al [28] reported the highest milk MAA concentration in ewes with subclinical mastitis comparing to healthy ewes (114.37 ± 41.14 vs. 29.68 ± 27.98 µg/mL).…”
Section: Acute-phase Proteinsmentioning
confidence: 99%